Multivariate Analysis of Lentil (Lens culinaris Medik.) under Three Rainfed Environments - Solanki, I S; Phogat, D S; Malik, B P S; Tomer, Y S (Annals of Arid Zone, 2016)
Thirty genotypes of lentil (Lens culinaris Medik.), collected from different eco-geographical regions, were used for multivariate analysis under three rainfed environments, viz., 1997-98 (E)), 1998-99 fE2) and 1999-2000 (Eo) at CCS HAU, Hisar. The data recorded for different characters (days to 50% tlowering. plant height, number of fruiting branchcs and pods planfl , 100-seed weight and seed yicld planfl) of each genotype were subjected to multivariate analysis using D2 statistics. The genotypcs were grouped into six clusters each in EI and E2, and scven clusters in Eo by adopting the Tocher's method. The constitution of different clusters with regard to the genotypes changed significantly in EI. E2 and Eo due to the G x E interaction. The clustering pattern dcpicted that the genetic diversity was not ncccssarily parallel to the geographic diversity. Taking into consideration the higher genetic divergence between different clusters, higher difference in cluster means for maximum number of charactcrs and per se performance of genotypes in all the environments. the crosses should be attempted bctween thc genotypes from c1u'stcrs II (LH 96-29. PL4. LH97-17 and LH97-25) and VI (L9-12) in E}, clusters V (LH82-6 and L4076) and VI (LH97-33) in E2 and clusters IV (LH 97-15 and LH 97-34) and VI (LH 84-8) in Eo.